A Multiple Antibiotic-Resistant Enterobacter cloacae Strain Isolated from a Bioethanol Fermentation Facility - Murphree, Colin A. (The Japanese Society of Microbial Ecology (JSME)/The Japanese Society of Soil Microbiology (JSSM), 2014)
An Enterobacter cloacae strain (E. cloacae F3S3) that was collected as part of a project to assess antibiotic resistance among bacteria isolated from bioethanol fermentation facilities demonstrated high levels of resistance to antibiotics added prophylactically to bioethanol fermentors. PCR assays revealed the presence of canonical genes encoding resistance to penicillin (ampC) and erythromycin (ermG). Assays measuring biofilm formation under antibiotic stress indicated that erythromycin induced biofilm formation in E. cloacae F3S3. Planktonic growth and biofilm formation were observed at a high ethanol content, indicating E. cloacae F3S3 can persist in a bioethanol fermentor under the highly variable environmental conditions found in fermentors.